Extraction of proteins from microalgae using integrated method of sugaring-out assisted liquid biphasic flotation (LBF) and ultrasound - Sankaran, Revathy; Manickam, Sivakumar; Yap, Yee Jiun; Ling, Tau Chuan; Chang, Jo-Shu; Show, Pau Loke (Elsevier, 2018)
In this study, a simple sugaring-out supported by liquid biphasic flotation technique combined with ultrasonication was introduced for the extraction of proteins from microalgae. Sugaring-out as a phase separation method is novel and has been used in the extraction of metal ions, biomolecules and drugs. But, its functioning in protein separation from microalgae is still unknown. In this work, the feasibility of sugaring-out coupled with ultrasound for the extraction of protein was investigated. Primary studies were carried out to examine the effect of sonication on the microalgae cell as well as the separation efficiency of the integrated method. Effect of various operating parameters such as the concentration of microalgae biomass, the location of sonication probe, sonication time, ultrasonic pulse mode (includes varying ON and OFF duration of sonication), concentration of glucose, types of sugar, concentration of acetonitrile and the flow rate in the flotation system for achieving a higher separation efficiency and yield of protein were assessed. Besides, a large-scale study of the integration method was conducted to verify the consistency of the followed technique. A maximum efficiency (86.38%) and yield (93.33%) were attained at the following optimized conditions: 0.6% biomass concentration, 200 g/L of glucose concentration, 100% acetonitrile concentration with 5 min of 5 s ON/10 s OFF pulse mode and at a flow rate of 100 cc/min. The results obtained for large scale were 85.25% and 92.24% for efficiency and yield respectively. The proposed liquid biphasic flotation assisted with ultrasound for protein separation employing sugaring-out demonstrates a high production and separation efficiency and is a cost-effective solution. More importantly, this method provides the possibility of extending its application for the extraction of other important biomolecules.